Deontological and Altruistic Guilt Feelings: A Dualistic Thesis - Mancini, Francesco; Gangemi, Amelia (Frontiers in Psychology, 2021)
In this paper, we argue in favor of the existence of two different guilt feelings: altruistic guilt (AG) and deontological guilt (DG). AG arises from having harmed, through one’s own action or omission, an innocent victim, while DG arises from the transgression of an internalized norm. In most daily experiences of guilt feelings, both types are present, but we argue that they are not traceable to each other and that each can be present without the other. We show that the two guilt feelings can be distinguished concerning behavioral, cognitive, and neurophysiological aspects. Moreover, we demonstrate that they are differently related to other processes and emotions. AG is connected with pain, empathy, and ToM. DG is strongly related to disgust. We briefly illustrate some implications for moral psychology and clinical psychology.